2006
DOI: 10.1161/01.hyp.0000248752.08807.4c
|View full text |Cite
|
Sign up to set email alerts
|

Uric Acid and the Development of Hypertension

Abstract: Abstract-Experimental evidence supports a causative role for uric acid in the pathogenesis of hypertension. Prospective studies have variably adjusted for relevant confounders and have been of relatively limited duration. We prospectively examined the relationship between uric acid level and the development of hypertension in the Normative Aging Study, a longitudinal cohort of healthy adult men. Key Words: uric acid Ⅲ hypertension Ⅲ renal function Ⅲ prospective studies Ⅲ aging T he association of hyperuricemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
108
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(115 citation statements)
references
References 41 publications
3
108
0
4
Order By: Relevance
“…40 Among the 2062 men free of hypertension in the Normative Aging Study for a 21-year follow-up period, uric acid increased newonset hypertension risk by 1.05-fold, 40 similar to our estimate in the multivariate model. We believe that most of the variables included in our models were feasible in the usual care practice in primary prevention settings.…”
Section: Table 4 Continuedsupporting
confidence: 79%
“…40 Among the 2062 men free of hypertension in the Normative Aging Study for a 21-year follow-up period, uric acid increased newonset hypertension risk by 1.05-fold, 40 similar to our estimate in the multivariate model. We believe that most of the variables included in our models were feasible in the usual care practice in primary prevention settings.…”
Section: Table 4 Continuedsupporting
confidence: 79%
“…MetS is characterized by the presence of multiple common cardiovascular risk factors, such as central obesity, atherogenic dyslipidemia (hypertriglyceridemia and low high-density lipoprotein cholesterol (HDL-C)) levels, hyperglycemia and elevated blood pressure (BP). Elevated SUA levels are prevalent in patients with hypertension 1,2 and MetS, [3][4][5][6][7] and these levels can be a significant predictor of the development of hypertension 3,[8][9][10] and MetS. [11][12][13][14] Although evidence has suggested that elevated SUA levels might have a role in hypertension, 15 a causal relationship has not been established.…”
Section: Introductionmentioning
confidence: 99%
“…Studies are necessary to understand the actual role they have in this scenario and whether they can actually be of value in the early identification of individuals at risk of developing CVD. Among these studies, is the one on uric acid (UA), which has behaved as a cardiovascular risk factor in several cross-sectional studies [1][2][3][4][5] . However, the presence of several confounding variables, such as obesity, alcohol consumption, age, diabetes and use of diuretics have made it difficult, to date, to indisputably practice, especially in individuals with metabolic syndrome and arterial hypertension.…”
Section: Introductionmentioning
confidence: 99%